Pelaksanaan dan Penegakkan Hak Asasi Manusia dan Demokrasi di Indonesia - Besar Besar (Humaniora, 2011)
The term human right shows that the power or authority a person has the fundamental nature. Number of cases of human rights violations that occur because of lack of understanding of the intrinsic value of every person so easily violate the rights of others. This violation is influenced by some cause. The most influential factors are political, economic, social, cultural and security. This research is examining the existing literature to find out about the importance of knowing human rights in everyday life in society and among students and to know more deeply about its relationship with democracy. The research methodology is explanatory; data used is data skunde namely from books. Based on research results, it can be concluded that the human rights needs to be communicated and implemented within the life of the community and among students. By knowing the obligations of their human rights and the implementation of human rights will be better again.